Rehabilitation nursing of integrated traditional Chinese and western medicine for a patient with neurogenic bladder (1例神经源性膀胱患者的中西医结合康复护理体会) - WANG Yueying (王月英); GE Fang (葛芳); ZHAO Ling (赵玲); WANG Fei (汪菲) (中西医结合护理)
This paper summarized the rehabilitation nursing of integrated traditional Chinese and western medicine for a patient with neurogenic bladder. Traditional Chinese Medicine nursing techniques such as acupuncture, acupoint wet-warm compress, and balanced cupping therapy were performed to strengthen the spleen, nourish the kidney and improve the physique. Moreover, comprehensive interventions such as symptom management, floor muscle function exercise, health education were carried out to establish a balanced vesicourethral function. The combination of appropriate health technology of Traditional Chinese Medicine and modern rehabilitation means is effective to relieve the symptoms of neurogenic bladder, relieve patient negative emotion, and improve the treatment compliance and recovery of bladder function. (本文总结1例神经源性膀胱(NB)的中西医结合康复护理经验。一方面通过针灸、穴位湿热敷、平衡火罐等中医适宜技术健脾补肾、行气利水、增强体质; 另一方面通过神经源性膀胱管理、盆底肌功能锻炼、健康教育等措施建立平衡的膀胱尿道功能。将中医适宜技术与现代康复手段相结合, 能有效改善患者NB症状, 缓解负性情绪, 增加治疗信心, 有助于膀胱功能的恢复和降低并发症发生风险。)